(untitled) (Global Journal of Science Frontier Research, 2023)
Wood density (WD) is not only a key element in tropical forest ecology to estimate tree biomass but also an indicator of timber quality, and it integrates many aspects of tree mechanical properties and functioning. Notably, contrasting patterns of radial variation of WD have been demonstrated and are related to regeneration guilds (light-demanding vs. shadebearing) but haven’t been demonstrated to be related to leaf phenology (deciduous vs. evergreen). With the destructive method and the "archimed" principle, we investigated the WD radial variation of nine timber tree species harvested in the eastern region of Cameroon. The result showed that WD differed significantly among these nine species (P > 0.05).